2019
DOI: 10.1038/s41419-019-1847-z
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of IRE1α RNase activity reduces NLRP3 inflammasome assembly and processing of pro-IL1β

Abstract: The inflammasome is a multiprotein complex assembled in response to Pathogen Associated Molecular Patterns (PAMPs) and Danger Associated Molecular Patterns (DAMPs). Inflammasome activation occurs through a two-step mechanism, with the first signal facilitating priming of inflammasome components while the second signal triggers complex assembly. Once assembled, the inflammasome recruits and activates pro-caspase-1, which in turn processes pro-interleukin (IL)-18 and pro-IL-1β into their bio-active forms. Owing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Although the IRE1-XBP-1 pathway is considered as being pro-survival mostly through its role in ER-associated degradation process during severe ER stress conditions, IRE1 may recruit TNF receptor-associated factor 2 and apoptosis signal-regulating kinase 1, then activate c-Jun N-terminal kinase (JNK) and induce apoptosis [20,21]. IRE-1-mediated activation of inflammasome leads to increased secretion of IL-1β and further IL-1, IL-6, and IL-8 [22]. IL-1α, as a crucial proinflammatory cytokine, has been reported to play dual function during ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although the IRE1-XBP-1 pathway is considered as being pro-survival mostly through its role in ER-associated degradation process during severe ER stress conditions, IRE1 may recruit TNF receptor-associated factor 2 and apoptosis signal-regulating kinase 1, then activate c-Jun N-terminal kinase (JNK) and induce apoptosis [20,21]. IRE-1-mediated activation of inflammasome leads to increased secretion of IL-1β and further IL-1, IL-6, and IL-8 [22]. IL-1α, as a crucial proinflammatory cytokine, has been reported to play dual function during ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of NLRP3 protein, adaptor protein apoptosisrelated speckles (ASC), and procaspase-1 [43,44]. The activation of NLRP3 inflammasome triggers the transformation of procaspase-1 to caspase-1 and catalyzes the exudation of mature IL-1β and IL-18 from pro-IL-1β and pro-IL-18, causing an inflammatory response [45,46]. Previous studies showed that ROS, especially from mitochondria, activated the NLRP3 inflammasome [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of NLRP3 protein, adaptor protein apoptosis-related speckles (ASC), and procaspase-1 [48,49]. The activation of NLRP3 inflammasome triggers the transformation of procaspase-1 to caspase-1 and catalyzes the exudation of mature IL-1β and IL-18 from pro-IL-1β and pro-IL-18, causing an inflammatory response [50,51]. Previous studies showed that ROS, especially from mitochondria, activated the NLRP3 inflammasome [52,53].…”
Section: Discussionmentioning
confidence: 99%